UNIVERSAL BASIC EDUCATION: A PANACEA FOR SOCIO-ECONOMIC AND POLITICAL DEVELOPMENT IN NIGERIA - Monsuru, Muraina B. (Sokoto Educational Review, 2020)
This paper examined the universal basic education (UBE) as a panacea for socio economic and political development in Nigeria. The paper observed that the major goals of the UBE such as numeric, Literacy and Acquisition of manipulating skills by people can help to modify Nigerian socio economic and political parochialism and thereby leading to socio economic and political development in Nigeria. Major objectives of the UBE programs were also examined. Recommendations were thereafter made on how to further enrich socio - economic and political development in Nigeria through Universal Basic Education, such as the need to employ qualified and zealous teachers to effectively implement the scheme.